ANALISIS KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2016 - DELVIA, VILLA DELVIA B1031131115 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACTThe research this purpose for know level potential bankruptcy and healthy to retail companies list on the bursa efek indonesia. The research this used method research descriptive. Data used this is annual finance report retail companies listed on the bursa efek Indonesia. Analysis tecniques used is Altman z-score method. In 2014 the category for companies located in the Gray Area there are 3 companies. Then companies that do not go bankrupt there are 7 companies. While for the year 2015 companies whose financial position in a healthy position or not bankrupt there are 7 companies, while in the gray area there are 3 companies. Then in the year 2016 companies in the gray area there are 4 companies, while for companies that do not go bankrupt there are 6. Keywords: Bankruptcy Analysis, Altman Z-Score Analysis